Determinants of going-concern audit opinions: evidence from Vietnam stock exchange-listed companies - Pham Duc Hieu (Cogent Economics & Finance, 2022)
In this study, we aim to examine the effect of company and auditor characteristics on the issuance of going-concern opinions. The study population encompasses all financially distressed manufacturing companies listed on the Vietnam Stock Exchange during 2010-2019. The results indicate that the financial condition, incurring loss, audit report delay, and frequency of the board of director meetings significantly influence the issuance of auditors' going-concern opinions. Company size, auditor size, and other financial ratios such as return on asset, leverage, and liquidity have no significant impact on the going-concern audit opinions. This study contributes to the limited research on going-concern audit opinions in the context of Vietnam. The results also provide a basis for recommendations to both auditors and audit clients on the determinants of going-concern audit opinions.
Keywords: 330; audit report; financial condition; going-concern audit opinion; Vietnam; Z-score